Locust-fungi success - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
In October 1990 SPORE reported on trials being conducted by CABl's International Institute of Biological Control using fungi as a biological control agent against grasshoppers and locusts (Spore 29 page 10). The pathogenic fungus Metarhizium...